Legal Protection for Consumers of Repackaged Powdered Milk under Consumer Protection Law and Food Safety Regulations - Salsabila Restia Putri; Ema Nurkhaerani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2026)
The increasing online sale of repackaged powdered milk has raised significant concerns regarding consumer protection and food safety in Indonesia. Although repackaging enables products to be marketed at lower prices, it frequently removes essential labeling information, including BPOM registration numbers, expiration dates, production codes, and manufacturer identity, thereby undermining product traceability and consumers’ right to accurate information. This study examines whether unauthorized repackaging constitutes a form of food product counterfeiting and evaluates the adequacy of Indonesia’s legal framework in protecting consumers under Law Number 8 of 1999 on Consumer Protection and BPOM Regulation Number 20 of 2021 on Processed Food Labels. Employing normative legal research through statutory and conceptual approaches, the study analyzes primary, secondary, and tertiary legal materials using qualitative methods. The findings demonstrate that unauthorized repackaging satisfies the legal characteristics of food product counterfeiting by altering product identity, facilitating unauthorized trademark use, and violating mandatory food-labeling requirements. While Indonesian law provides administrative, civil, and criminal remedies alongside regulatory oversight by BPOM, enforcement remains constrained by limited supervision of digital marketplaces and inadequate consumer awareness. This study contributes to consumer protection scholarship by clarifying the legal classification of repackaged powdered milk and highlighting regulatory challenges posed by the rapid expansion of e-commerce.